1997
DOI: 10.1074/jbc.272.35.22322
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Patterns of CpG Island Methylation in Normal and Neoplastic Cells Implicates Both Upstream and Downstream Regions inde Novo Methylation

Abstract: Promoter region CpG island methylation is associated with tumor suppressor gene silencing in neoplasia. GenBank sequence analyses revealed that a number of CpG islands are juxtaposed to multiple Alu repeats, which have been proposed as "de novo methylation centers." These islands also contain multiple Sp1 elements located upstream and downstream of transcription start, which have been shown to protect CpG islands from methylation. We mapped the methylation patterns of the E-cadherin (E-cad) and von Hippel-Lind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
188
1
1

Year Published

1998
1998
2009
2009

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 285 publications
(205 citation statements)
references
References 24 publications
15
188
1
1
Order By: Relevance
“…However, methylation within non-CpG island regions is thought to contribute to the maintenance of a heterochromatinized state which precludes binding of transcription factors (Tate and Bird, 1993;Antequera et al, 1990;Nan et al, 1996). Since it has been shown that CpG dinucleotides in bulk chromatin outside CpG-islands may become hypomethylated in some tumours, altered methylation within this NF1 region could compromise the gene's structural integrity and alter NF1 expression (Gra et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, methylation within non-CpG island regions is thought to contribute to the maintenance of a heterochromatinized state which precludes binding of transcription factors (Tate and Bird, 1993;Antequera et al, 1990;Nan et al, 1996). Since it has been shown that CpG dinucleotides in bulk chromatin outside CpG-islands may become hypomethylated in some tumours, altered methylation within this NF1 region could compromise the gene's structural integrity and alter NF1 expression (Gra et al, 1997).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies in the literature point to a potential role for SP1 binding sites in maintaining the CpG island in an unmethylated and transcriptionally active state (Gra et al, 1997;Clark et al, 1997;Macleod et al, 1994;Brandeis et al, 1994). In contrast to many other transcription factors, SP1 has until recently been shown to bind to its recognition sequence regardless of its methylation status.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, this CpG island has been described as a hallmark of promoter methylation in human cancers. 24,25 CDH1 promoter methylation analysis was performed in all tumor DNA samples. The EpiTect Bisulfite Kit (Qiagen, Valencia, Calif) was used to treat 200 ng of DNA.…”
Section: Cdh1 Promoter Methylation Analysismentioning
confidence: 99%